Applications of item response theory to measuring the safety response competency of workers in subway construction projects. (July 2020) - Zhou, Zhipeng; Guo, Wenya
Highlights: IRT was used to measure safety response competency of subway construction labors. Safety response competency of most workers was in low or moderate levels. Safety response competency and some demographic variables were not correlated. Ten questions were divided as high and low discrimination with moderate difficulty. Training should be customized for workers with unequal safety response competency. Abstract: Ceaseless construction accidents seriously influence the sustainable development of subway infrastructure projects. Unsafe behavior regarded as the major accident causation is the external manifestation of insufficient competency in safety response. Main aim of this study is to employ item response theory (IRT) towards a quantitative framework to measure safety response competency of individual labor at subway construction sites. A total of forty-three questionnaires were collected from three types of subway construction workers of shield machine operators, segment erectors and machinery maintenance laborers. The findings signified that only one worker had a high level of safety response competency. The other workers' safety response competencies were in the levels of low or moderate. Ten situational questions in the questionnaire were analyzed and classified according to discrimination and difficulty parameters, which is benefit of customizing safety training programs for site workers with unequal safety response competency in subway projects.